2017
DOI: 10.1080/15332640.2017.1300552
|View full text |Cite
|
Sign up to set email alerts
|

Strength in the midst of pain: Abuse as a predictor of sexual relationship power among substance-abusing Black women

Abstract: The aim of this research was to explore the association of abuse experiences (child sexual abuse and adult physical/sexual violence) to sexual relationship power among Black substance-abusing women. The study was a secondary analysis of baseline data collected from 124 Black women in 12 drug treatment programs across the United States who initially participated in an HIV risk reduction trial conducted within the National Drug Abuse Treatment Clinical Trials Network of the National Institute on Drug Abuse (NIDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Regarding HIV and risky sexual behaviors among Black women, Ahuama-Jonas, Burlew, Campbell, and Tross (2017) found that a history of sex abuse jeopardizes the sexual relationship power that women may need to protect themselves. However, among Black men, the endorsement of stereotypical masculinity roles appears to be associated with more unprotected sexual occasions with casual partners (Wilson et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding HIV and risky sexual behaviors among Black women, Ahuama-Jonas, Burlew, Campbell, and Tross (2017) found that a history of sex abuse jeopardizes the sexual relationship power that women may need to protect themselves. However, among Black men, the endorsement of stereotypical masculinity roles appears to be associated with more unprotected sexual occasions with casual partners (Wilson et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…SRP has been found to be associated with dating violence, IPV, and risky sexual behavior (McMahon et al, 2015). Among women who use substances, specifically, low SRP is associated with increased substance use, having a partner who injects drugs, risky sexual behaviors, and interpersonal violence (Ahuama-Jonas et al, 2017;A. N. C. Campbell et al, 2012;Staton et al, 2017).…”
Section: Maltreatment and Relationships: The Role Of Srpmentioning
confidence: 99%
“…SRP has been found to be associated with dating violence, IPV, and risky sexual behavior (McMahon et al., 2015). Among women who use substances, specifically, low SRP is associated with increased substance use, having a partner who injects drugs, risky sexual behaviors, and interpersonal violence (Ahuama‐Jonas et al., 2017; A. N. C. Campbell et al., 2012; Staton et al., 2017). Given the high prevalence of risky sexual and substance use behaviors among justice‐involved women (Staton et al., 2017), it is important to understand SRP in samples of justice‐involved women with substance use disorders, including OUD.…”
Section: Maltreatment and Trauma Among Justice‐involved Women With Su...mentioning
confidence: 99%
“…Despite the fact that the SSSB group reported 29% fewer unprotected sexual occasions than the control group after participating in the intervention, unprotected sexual occasions remained unacceptably high for all participants. Based on evidence of racial/ethnic differences in sexual risk factors (Ahuama-Jonas, Burlew, Campbell, & Tross, 2017), we opted to attempt to further reduce sexual risk factors among Black women who use substances by culturally adapting the original SSSB intervention to include more culturally specific content.…”
Section: Application Of Theater Testing To Adapt Sssbmentioning
confidence: 99%